Social Political Roots of Leadership Power In Ulu Malay Lampik Empat Merdike Duwe - Mohammad Syawaludin (UIN Sunan Gunung Djati, 2023)
Traditional leadership in modern societies still influences decisions made and social behavior. Emerging influences can be specific values, norms, beliefs, leadership, and knowledge. In the face of social change, even traditional identities are characterized as moral rituals. One is Lampik Empat Merdike Duwe, his four in the leadership tradition of Jagat Besemah. This practice is an ethical standard maintained and passed down in the Basemah community. Phenomenological and qualitative methods were used to interpretively analyze behavioral properties, values, norms, and knowledge data. Using theories of formative and constructive and cultural transformation, the forces and influences of civilization can be divided into three fundamental parts: social, cultural, and behavioral systems. The three methods are interrelated to form a dynamic space based on reference and action. The study found that Lampik empat merdike duwe leadership was socioculturally unable to function in the local leadership power space and only became a moral standard for the Besemah community. The Lampik EmpatÂ Â Merdike Duwe concept of power is more similar to the attribution and attainment status models. Attribution status is the social status given to a person by birth or genetic affiliation. A person cannot choose or achieve this status but is